Peran Pengawasan Otoritas Jasa Keuangan Terhadap Pinjaman Online Berdasarkan Undang-Undang Nomor 21 Tahun 2011 - Purba, Calvin Axel; Khairunnisa, ‘Imarroh Lutfiyatul Laeli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
One of OJK's steps in regulating this sector is through OJK Regulation Number 77/POJK.01/2016 concerning Information Technology-Based Money Lending Services. This regulation provides detailed provisions regarding the implementation of online loan services as well as educational obligations for the public to increase knowledge and understanding of financial institutions, financial products, and financial services (Mohammad Amin El Fajri, 2018). However, because there are still many illegal online loan practices, OJK is actively eradicating illegal online loan providers. This study is a qualitative descriptive study with a normative perspective. The main data is obtained from the results of a literature review. Data analysis uses qualitative analysis. The results of the study show that the supervision carried out by OJK so far has had a positive impact, especially in increasing the sense of security and legal protection for consumers, raising public awareness of their rights, and encouraging industry players to carry out healthy business practices. However, challenges such as the rise of illegal online loans, illegal collection practices, weak supervision of third parties, and the transfer of some regulatory authority to industry associations, indicate that the OJK needs to continue to update and strengthen regulations that are more assertive, systemic, and integrated.